2021
DOI: 10.1161/jaha.120.019811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Active Cancer on the Cardiac Phenotype: A Cardiac Magnetic Resonance Imaging‐Based Study of Myocardial Tissue Health and Deformation in Patients With Chemotherapy‐Naïve Cancer

Abstract: Background The overlap between cancer and cardiovascular care continues to expand, with intersections emerging before, during, and following cancer therapies. To date, emphasis has been placed on how cancer therapeutics influence downstream cardiac health. However, whether active malignancy itself influences chamber volumes, function, or overall myocardial tissue health remains uncertain. We sought to perform a comprehensive cardiovascular magnetic resonance‐based evaluation of cardiac health in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
1
19
1
Order By: Relevance
“…Most previously conducted animal studies emphasize how cancer therapeutics promote inflammation or cardiac dysfunction, while the effects of cancer development are not well researched. Intriguingly, cancer itself can affect cardiovascular health through independent signaling pathways other than those triggered by cancer treatment [58]. In a recent clinical study, chemotherapy-naive patients with newly diagnosed lymphoma demonstrated reduced cardiac chamber volumes compared to healthy volunteers [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previously conducted animal studies emphasize how cancer therapeutics promote inflammation or cardiac dysfunction, while the effects of cancer development are not well researched. Intriguingly, cancer itself can affect cardiovascular health through independent signaling pathways other than those triggered by cancer treatment [58]. In a recent clinical study, chemotherapy-naive patients with newly diagnosed lymphoma demonstrated reduced cardiac chamber volumes compared to healthy volunteers [58].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, cancer itself can affect cardiovascular health through independent signaling pathways other than those triggered by cancer treatment [58]. In a recent clinical study, chemotherapy-naive patients with newly diagnosed lymphoma demonstrated reduced cardiac chamber volumes compared to healthy volunteers [58]. One of the suggested pathways in which cancer could affect the heart is through cancer-induced inflammation [59].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study during follow up with cancer patients, Pavo et al [77] demonstrated that myocardial damage indicated the augmented expression of cardiovascular functional peptides and morphological markers might be responsible for disease progression and lead to increased mortality in cancer patients [77]. A multicomponent cardiovascular resonance imaging study revealed that cancer itself could modulate the morphology and function of the heart (chamber volume, ejection fraction and native T1 mapping) in naïve breast cancer or lymphoma patients [78]. A study based on the data collected from 7.5 million cancer patients from the National Cancer Institute's Surveillance, Epidemiology, and End Results (SEER) program revealed that cancer patients are more prone to develop fatal heart disease with a standardized mortality ratio (SMR) of 2.4.…”
Section: Cancer Induced Cardiac Cachexia: Experimental and Clinical E...mentioning
confidence: 99%
“…In addition, recent evidence suggests that already at the time of diagnosis, patients with de novo cancers have abnormal cardiovascular imaging characteristics, as defined by cardiac magnetic resonance imaging, including smaller chamber sizes, increased strain amplitude, and systolic strain rate, and therefore various cardiovascular phenotypes will invariably exist in a given cohort of cancer patients. 72 Second, narrow eligibility criteria compound the evaluation of drug‐drug and drug‐disease interactions, which is vital to the development of safe pharmacologic treatment practices. For example, epidermal growth factor receptor inhibitors are a cornerstone in the treatment of patients with advanced lung adenocarcinoma who harbor epidermal growth factor receptor mutations but may prolong the QT interval.…”
Section: Inclusion Of Patients With Cardiovascular Disease In Oncolog...mentioning
confidence: 99%